Challenges and practices in international sport federations to gain and maintain legitimacy - Josephine Clausen; Emmanuel Bayle (Bern Open Publishing, 2024)
Introduction International sport federations (IFs) are today part of complex ecosystems (Bayle, 2023). As governing bodies, they are regulators and define and sanction sporting and participation rules. IFs are further organizers of international sport events, some of which attract large audiences and investments. In this role, IFs have to satisfy diverging demands of multiple stakeholders (Chappelet, 2021). Additionally, IFs have become important social, economic and political actors. They are employers and as such contribute to the local economy and have a corporate social responsibility. And with sport being increasingly interwoven with money, power, politics and state interests, IFs also influence and are influenced by geopolitics. This has entailed corruption and self-enrichment on one side of the spectrum, and it enabled peace processes and development on the other side. In this complex web of mission, expectations and pressures, how do IFs gain/maintain legitimation? Methods Using literature research and desk research, we first focus on the role and mission of IFs since their creation and illustrate an overview of the changing expectations against which IFs sought/seek legitimacy (historical timeline). Reflecting the conceptual model of Bayle and Clausen (2023, under review) on IFs' organizational performance and its operationalization, we then map explicit and implicit performance indicators that derive from IFs' mission and the multiple social, economic and political activities they have embraced over the past decades. Based on this mapping, we discuss IFs' strategies to meet expectations and pressures that result from these performance indicators. We conclude the presentation with an assessment of the interrelation between expectations towards IFs, strategies developed by IFs, and internal/external performance control mechanisms based on five interviews. Results The social, political, and economic influence of IFs is largely recognized today. Yet, their legitimacy as non-profit governing bodies of sport in the eyes of prominent stakeholders (e.g., IOC, governments, sponsors) is currently reduced to their ability to comply with dominant governance and sustainability frameworks. As a result of this narrow focus, academics and practitioners have developed a good understanding and monitoring mechanisms of IFs' governance practices. On the other hand, IFs' performance and legitimacy from a mission and purpose perspective is greatly understudied. Discussion/Conclusion One of the challenges in defining performance indicators for IFs is their broad societal mission. Firstly, the impact of IFs' activities to contribute to some sort of societal betterment is difficult to measure. And secondly, the priorities of societal issues change (e.g., poverty, health, climate). Any performance measurement system for IFs therefore needs to be dynamic to address both IFs' mission and evolving external expectations. References Bayle, E. (2023). A model for the multi-centered regulation of world sport. International Journal of Sport Policy and Politics, 15(2), 309-327. https://doi.org/10.1080/19406940.2023.2205868 Bayle, E., & Clausen, J. (2023, under review). A conceptual model to understand and assess international sport federations' organizational performance. Journal of Global Sport Management. Chappelet, J. L. (2021). The governance of the Olympic system: From one to many stakeholders. Journal of Global Sport Management 8(4), 783-800. https://doi.org/10.1080/24704067.2021.1899767